A murder is announced - Christie, Agatha (HarperCollins London, 2005)
A facsimile first edition hardback of the Miss Marple books, published to mark the 75th anniversary of her first appearance and to celebrate her new-found success on television. The villagers of Chipping Cleghorn are agog with curiosity over an advertisement in the local gazette which reads: 'A murder is announced and will take place on Friday, September 25th, at Little Paddocks at 7.30pm.' A childish practical joke? Or a hoax intended to terrify poor Letitia Blacklock? Unable to resist the mysterious invitation, a crowd begins to gather at Little Paddocks at the appointed time when, without warning, the lights go out, a man bursts into the room and fires three shots ... Miss Marple, visiting an old friend in the village, can't resist joining the investigation